Brown red flexible electrochromic assembly and preparation method thereof

By designing a multilayer structure on a flexible substrate and packaging material, combining Li+ doped Zn(PO4)x gel and WO3/PEDOT:PSS composite electrochromic layer, the rigidity and limited color of existing electrochromic components are solved. Problem, the electrochromic effect with flexible high color saturation and long life is achieved, and is suitable for multi-field applications.

CN119247660AInactive Publication Date: 2025-01-03CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411564769.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing electrochromic components are limited in their applications in smart windows, displays and other optoelectronic devices due to their limited rigidity and color variation, and are particularly lacking in flexibility and multi-color performance.

Method used

Using flexible substrates and packaging materials, combined with transparent conductive layer, electrochromic layer, ionic storage layer and multi-layer dielectric layer, brown-red flexible electrochromic components are prepared by spin coating and radio frequency sputtering processes, using Li+ doped Zn( PO4)x gel and WO3/PEDOT:PSS composite electrochromic layer to achieve structural color and high color saturation.

Benefits of technology

It realizes flexibility and high dimensional flexibility, does not reduce color discoloration effect, improves the cycle life and ion conduction efficiency of electrochromic components, reduces production costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119247660A_ABST
    Figure CN119247660A_ABST
Patent Text Reader

Abstract

The invention discloses a brownish red flexible electrochromic assembly and a preparation method thereof, and belongs to the technical field of flexible electrochromism. The prepared electrochromic assembly comprises a flexible substrate, a working electrode, an electrolyte, a counter electrode and a flexible packaging material with a structural color, the structural color is prepared on the flexible packaging material, so that the assembly is endowed with color and color changing effects; the production cost of the assembly is effectively reduced by adopting a full-liquid-phase coating process; the Li < + > doped Zn (PO4) x gel is adopted, so that the ion conduction efficiency of the electrolyte layer can be effectively improved, and the cycle life of the electrochromic assembly can be prolonged; the composite color-changing layer enables the assembly to be high in color saturation and not easy to fade; therefore, the prepared electrochromic assembly is high in flexibility, flexible in size, multiple in color variety, high in saturation degree, not prone to color fading, long in cycle life and high in ion conduction efficiency; and the preparation process is simple, large-scale production operation is easy, and the preparation method has important application value in the technical field of flexible electrochromism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flexible electrochromic technology, and in particular, relates to a brown-red flexible electrochromic component and a preparation method thereof. Background Art

[0002] Electrochromism refers to the phenomenon that a material reversibly changes its color or optical properties through a redox reaction under the action of an applied voltage or current. Compared with traditional polymer dispersed liquid crystal devices, electrochromic components have more advantages in the fields of smart windows, displays, anti-glare rearview mirrors and other optoelectronic devices due to their low energy consumption, non-radiation and long-term stability.

[0003] At present, most electrochromic components are rigid due to the use of transparent conductive glass as the substrate material, but this inevitably brings about problems such as brittleness and inflexible size of the components, thus limiting the potential application of rigid electrochromic components in many fields. In addition, the color of commonly used electrochromic components is determined by the electronic structure and optical properties of the electrochromic material itself, and the color change is limited, which also greatly limits the application field of electrochromic components. Therefore, combining structural color and electrochromic materials in some way can make the electrochromic material show a color different from its intrinsic color.

[0004] Patent CN11624829A "Multicolor electrochromic structure, its preparation method and application" adopts the method of setting a first reflective surface and a second reflective surface on the electrochromic layer, and the first reflective surface and the second reflective surface are provided with a dielectric layer, and a multi-color is formed by an optical cavity composed of the first reflective surface, the second reflective surface and the dielectric layer. Patent CN114859611B "A multicolor electrochromic film, device and preparation method" introduces an electrochromic layer of a porous metal oxide V2O5 combined with an ion conductor layer of a liquid electrolyte to finally obtain a multicolor electrochromic device. First of all, the multicolor components obtained in the above-mentioned public patents are all obtained by improving the electrochromic functional layer, which requires the electrochromic functional layer to have not only the function of electrochromism but also different colors. However, considering the two functions when designing electrochromic devices will greatly affect the efficiency of electrochromism. In addition, the above-mentioned patents are all for rigid electrochromic devices, and the lack of consideration for flexible devices also greatly reduces their application fields. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a brown-red flexible electrochromic component and a preparation method thereof.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A brown-red flexible electrochromic component comprises a flexible substrate, a working electrode, an electrolyte, a counter electrode and a flexible packaging material with structural color; the working electrode comprises a first transparent conductive layer and an electrochromic layer, which are sequentially deposited on the flexible substrate; the electrolyte is located between the composite color-changing layer and the ion storage layer; the counter electrode comprises an ion storage layer and a second transparent conductive layer, which are sequentially deposited on one side of the flexible packaging material with structural color; the other side of the flexible packaging material with structural color is provided with a first high refractive index medium layer, a second low refractive index medium layer, an amorphous silicon layer and a third low refractive index medium layer in sequence from inside to outside.

[0008] Furthermore, the flexible substrate and the flexible packaging material are one of flexible glass, PI and PET.

[0009] Furthermore, the electrolyte is Li + Doped Zn(PO 4 ) x Gel, thickness is 300-600nm.

[0010] Furthermore, the first transparent conductive layer and the second transparent conductive layer are both transparent conductive films made of Ag or Cu nanowires, with a thickness of 100-200 nm.

[0011] Furthermore, the electrochromic layer is WO 3 and a PEDOT:PSS composite electrochromic layer with a thickness of 150-300 nm.

[0012] Furthermore, the ion storage layer is composed of monodisperse nano-sized NiO X NiO particles X Electrochromic film, thickness is 200-400nm.

[0013] Furthermore, the first high refractive index medium layer is ZrO X N Y The film has a refractive index range of 1.7-2.2 and a thickness of 150-200nm.

[0014] Furthermore, the second and third low refractive index medium layers are SiO X N Y The film has a refractive index ranging from 1.5 to 2.0; the second low-refractive-index medium layer has a thickness of 10 to 50 nm, and the third low-refractive-index medium layer has a thickness of 100 to 150 nm.

[0015] Furthermore, the amorphous silicon layer has a thickness of 5-20 nm.

[0016] A method for preparing a brown-red flexible electrochromic component comprises the following steps:

[0017] S1. Select a flexible substrate, prepare a 2-6 mol / L Ag or Cu nanowire solution, deposit it on the substrate by spin coating, and heat treat and solidify to obtain a transparent conductive film as the first transparent conductive layer. 3 / PEDOT:PSS mixed precursor solution is deposited on the first transparent conductive layer by spin coating process, and the electrochromic layer is obtained after heat treatment and curing, thereby obtaining a flexible substrate for depositing the working electrode;

[0018] S2, prepare a 2-6 mol / L Ag or Cu nanowire solution, select one side of the flexible packaging material to deposit by spin coating, heat treat and solidify to obtain a transparent conductive film as the second transparent conductive layer, and coat NiO X The precursor solution is deposited on the second transparent conductive layer by spin coating process, and the ion storage layer is obtained after heat treatment and curing. The first high refractive index dielectric layer ZrO is prepared on the other side of the flexible packaging material by radio frequency reactive sputtering process. X N Y The second and third low refractive index dielectric layers SiO are prepared by radio frequency reactive sputtering process. X N Y thin film, depositing an amorphous silicon layer on the surface of the second low-refractive index dielectric layer using an ion-assisted deposition electron beam evaporation process to obtain a flexible packaging material with structural color for depositing a counter electrode;

[0019] S3. Preparation of electrolyte: n-butanol, zinc acetate, lithium perchlorate and phosphoric acid were mixed and dissolved into a precursor solution by wet chemical sol-gel method, and Li + Doped Zn(PO 4 ) x gel;

[0020] S4, the flexible substrate for depositing the working electrode prepared in step S1 and the flexible packaging material for depositing the counter electrode with structural color prepared in step S2 are coated with Li + Doped Zn(PO 4 ) x The components are bonded together using gel as a medium, and then heat-treated to cure the wet chemical ion transport layer in the middle of the component and seal the surrounding frames with butyl glue to obtain a brown-red flexible electrochromic component.

[0021] Furthermore, in step S1, WO 3 / PEDOT:PSS mixed precursor solution is composed of WO 3 , PEDOT:PSS, acetylacetone and isopropanol are fully mixed and dissolved in a weight ratio of 16:1:1:3.

[0022] Furthermore, the spin coating speed of the spin coating process in steps S1 and S2 is 500-3000 r / s, and the thermal curing temperature is 50-200°C.

[0023] Furthermore, in step S2, NiO X The precursor solution consists of monodispersed nanosized NiO X Particles, H 2 O 2 The obtained product is obtained by fully mixing and dissolving with anhydrous ethanol in a weight ratio of 5:10:20.

[0024] Furthermore, in step S2, the RF sputtering power is 100-300 W, and the working pressure is 2-12×10 -1 Pa, Ar flow rate is 30sccm, O 2 The flow rate is 1-10sccm.

[0025] Furthermore, the working pressure of the ion-assisted deposition electron beam evaporation in step S2 is 1-1.5×10 -3 Pa, the electron gun voltage is 5-10kV, and the substrate temperature is 50-150℃.

[0026] Furthermore, in step S3, the weight ratio of zinc acetate, lithium perchlorate and phosphoric acid is 30:10:6:18.

[0027] Furthermore, the evaporation temperature in step S3 is 100-150°C.

[0028] Furthermore, the heat treatment temperature in step S4 is 40-60°C.

[0029] By preparing structural colors on flexible packaging materials, the electrochromic components are given colors without reducing the color changing effect of the components. The working electrode, counter electrode and electrolyte are prepared by the full liquid phase coating process, which effectively reduces the production cost of the components. 3 and PEDOT:PSS composite color-changing layer, so that the color-changing component has high color saturation and is not easy to fade; the prepared Li + Doped Zn(PO 4 ) x The gel greatly increases the Li + The conduction can effectively improve the ion conduction efficiency of the electrolyte layer and extend the cycle life of the electrochromic component.

[0030] Beneficial effects of the present invention:

[0031] The electrochromic component prepared by the invention comprises a flexible substrate, a working electrode, an electrolyte, a counter electrode and a flexible packaging material with structural color;

[0032] 1. By preparing structural colors on flexible packaging materials, the electrochromic components are given colors without reducing the color-changing effect of the components;

[0033] 2. The working electrode, counter electrode and electrolyte are prepared by full liquid phase coating process, which effectively reduces the production cost of components;

[0034] 3. Use Li + Doped Zn(PO 4 ) x Gel can greatly increase Li + The conduction of ions can effectively improve the ion conduction efficiency of the electrolyte layer and extend the cycle life of the electrochromic component;

[0035] 4. Combined with WO 3 The PEDOT:PSS composite color-changing layer makes the component highly color saturated and not easy to fade;

[0036] Therefore, the electrochromic component prepared by the present invention is highly flexible and flexible in size. The color of the electrochromic component does not reduce the color changing effect of the component, is not easy to age and lose color, and effectively improves the ion conduction efficiency of its electrolyte layer, prolongs the overall cycle life of the component, is easy to mass produce, and has important application value in the field of flexible electrochromic technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The present invention will be further described below in conjunction with the accompanying drawings.

[0038] Figure 1 It is a schematic structural diagram of a brown-red flexible electrochromic component of the present invention;

[0039] Figure 2 This is a colored diagram of the actual component obtained in Example 1 of the present invention;

[0040] Figure 3 This is a fading state diagram of an actual component prepared in Example 1 of the present invention;

[0041] Figure 4 The relationship between the number of cycles and the transmittance of the actual component prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] like Figure 1As shown, the present invention provides a brown-red flexible electrochromic component, comprising a flexible substrate 1, a working electrode 2, an electrolyte 3, a counter electrode 4 and a flexible packaging material 5 with structural color, the working electrode 2 comprises a first transparent conductive layer 6 and an electrochromic layer 7, the counter electrode 4 comprises an ion storage layer 8 and a second transparent conductive layer 9, and the other side of the flexible packaging material 5 is provided with a first high refractive index medium layer 10, a second low refractive index medium layer 11, an amorphous silicon layer 12 and a third low refractive index medium layer 13 in sequence from the inside to the outside.

[0044] Example 1

[0045] S1. Select flexible glass with a thickness of 30 μm as the substrate, mix 10 g of Ag nanowires, 5 g of polysiloxane and 40 g of anhydrous ethanol to obtain a 2 mol / L Ag nanowire solution, and use a spin coating process to spin coat the flexible glass at a speed of 3000 r / s, a spin coating time of 20 s, a thermal curing temperature of 50 ° C, and a curing time of 5 min to obtain a transparent conductive film with a thickness of 100 nm. 3 WO was obtained by mixing and dissolving 1 g PEDOT:PSS, 1 g acetylacetone and 3 g isopropanol. 3 / PEDOT:PSS mixed precursor solution was deposited on the first transparent conductive layer by spin coating process, the spin coating speed was 2000r / s, the spin coating time was 25s, the thermal curing temperature was 70℃, the curing time was 5min, and a composite electrochromic layer with a thickness of 150nm was obtained, which was the flexible substrate for depositing the working electrode;

[0046] S2. Select flexible glass with a thickness of 30 μm as the flexible packaging material, mix 10 g of Ag nanowires, 5 g of polysiloxane and 40 g of anhydrous ethanol to obtain a 2 mol / L Ag nanowire solution, and spin coat it on one side of the flexible glass using a spin coating process. The spin coating speed is 3000 r / s, the spin coating time is 20 s, the thermal curing temperature is 50 ° C, and the curing time is 5 min to obtain a transparent conductive film with a thickness of 100 nm. 90 20nm NiO X Granules, 10gH 2 O 2 After being fully mixed and dissolved with 20g of anhydrous ethanol, NiO X The precursor solution was deposited on the second transparent conductive layer by spin coating process, with a spin coating speed of 1500 r / s, a spin coating time of 30 s, a thermal curing temperature of 85 ° C, and a curing time of 6 min to obtain a NiO layer with a thickness of 200 nm. X Ion storage layer. On the other side of the flexible glass, the first high refractive index dielectric layer is prepared by radio frequency reactive sputtering process, the sputtering target is ZrN ceramic target, the sputtering process gas is Ar, and the reaction gas is O2 , the working pressure is 5×10 -1 Pa, sputtering power is 200w, Ar flow rate is 30sccm, O 2 The flow rate is 5 sccm, the sputtering time is 40 min, and the first high refractive index dielectric layer with a refractive index of 2.0 and a thickness of 170 nm is obtained. The second low refractive index dielectric layer is prepared on the surface of the first high refractive index dielectric layer by radio frequency reactive sputtering process, and the sputtering target material is Si 3 N 4 Ceramic target, sputtering process gas is Ar, reaction gas is O 2 , the working pressure is 7×10 -1 Pa, sputtering power is 150w, Ar flow rate is 30sccm, O 2 The flow rate was 4 sccm, and the deposition time of the second low refractive index dielectric layer was 6 min, resulting in a second low refractive index dielectric layer with a refractive index of 1.8 and a thickness of 30 nm. The amorphous silicon layer was deposited on the surface of the second low refractive index dielectric layer using ion-assisted deposition electron beam evaporation process. The film material used was Si particles with a purity of 99.99%, the ion source gas was Ar with a purity of 99.99%, and the working pressure was 1×10 -3 Pa, the electron gun voltage is 5kV, the substrate temperature is 50℃, and the deposition time is 8min. An amorphous silicon layer with a refractive index of 4.1 and a thickness of 5nm is obtained. The third low refractive index dielectric layer is deposited on the surface of the amorphous silicon layer by radio frequency reactive sputtering process. The sputtering target material is Si 3 N 4 Ceramic target, sputtering process gas is Ar, reaction gas is O 2 , the working pressure is 3×10 -1 Pa, sputtering power is 100w, Ar flow rate is 30sccm, O 2 The flow rate is 1 sccm, and the time for depositing the third low refractive index medium layer 6 is 20 minutes, so as to obtain a third low refractive index medium layer with a refractive index of 2.0 and a thickness of 100 nm, which is a flexible packaging material with structural color for depositing the counter electrode;

[0047] S3. Preparation of electrolyte: Using wet chemical sol-gel method, 30g n-butanol, 10g zinc acetate, 6g lithium perchlorate, and 18g phosphoric acid were mixed and dissolved to form a precursor solution, which was hydrolyzed and precipitated at room temperature to form a sol. After standing for 5 hours, it was evaporated at 100°C for 5 minutes to obtain a 600nm thick Li + Doped Zn(PO 4 ) x gel;

[0048] S4, the flexible substrate for depositing the working electrode prepared in step S1 and the flexible packaging material for depositing the counter electrode with structural color prepared in step S2 are coated with Li +Doped Zn(PO 4 ) x The gel is used as a medium to bond together, and then a heat treatment is performed at 40°C to cure the wet chemical ion transport layer in the middle of the component for 15 minutes, and the surrounding frames are sealed with butyl glue to obtain a brown-red flexible electrochromic component.

[0049] Example 2

[0050] S1. Select flexible PI as the substrate, mix 20g Cu nanowires, 5g polysiloxane and 40g anhydrous ethanol to obtain a 4mol / L Cu nanowire solution, and spin coat it on the flexible PI by spin coating. The spin coating speed is 1500r / s, the spin coating time is 25s, the thermal curing temperature is 100℃, and the curing time is 7min. A transparent conductive film with a thickness of 150nm is obtained. 16g WO 3 WO was obtained by mixing and dissolving 1 g PEDOT:PSS, 1 g acetylacetone and 3 g isopropanol. 3 / PEDOT:PSS mixed precursor solution was deposited on the first transparent conductive layer by spin coating process, the spin coating speed was 1200r / s, the spin coating time was 30s, the thermal curing temperature was 110℃, the curing time was 8min, and a composite electrochromic layer with a thickness of 210nm was obtained, which was the flexible substrate for depositing the working electrode;

[0051] S2, select flexible glass with a thickness of 30μm as flexible packaging material, mix 20g Ag nanowires, 5g polysiloxane and 40g anhydrous ethanol to obtain a Cu nanowire solution with a concentration of 4mol / L, and use spin coating process to spin coat on one side of the flexible glass, the spin coating speed is 1500r / s, the spin coating time is 25s, the thermal curing temperature is 100℃, the curing time is 7min, and a transparent conductive film with a thickness of 150nm is obtained. 90 15nm NiO X Granules, 10gH 2 O 2 After being fully mixed and dissolved with 20g of anhydrous ethanol, NiO X The precursor solution was deposited on the second transparent conductive layer by spin coating process, with a spin coating speed of 1000 r / s, a spin coating time of 35 s, a thermal curing temperature of 90 ° C, and a curing time of 7 min to obtain a NiO layer with a thickness of 350 nm. X Ion storage layer. On the other side of the flexible glass, the first high refractive index dielectric layer is prepared by radio frequency reactive sputtering process, the sputtering target is ZrN ceramic target, the sputtering process gas is Ar, and the reaction gas is O 2 , the working pressure is 12×10 -1 Pa, sputtering power is 300w, Ar flow rate is 30sccm, O 2The flow rate was 10 sccm, the sputtering time was 35 min, and the first high refractive index dielectric layer with a refractive index of 2.2 and a thickness of 200 nm was obtained. The second low refractive index dielectric layer was prepared on the surface of the first high refractive index dielectric layer by radio frequency reactive sputtering process, and the sputtering target material was Si 3 N 4 Ceramic target, sputtering process gas is Ar, reaction gas is O 2 , the working pressure is 3×10 -1 Pa, sputtering power is 100w, Ar flow rate is 30sccm, O 2 The flow rate is 1 sccm, and the deposition time of the second low refractive index medium layer 4 is 2 min, and the second low refractive index medium layer with a refractive index of 2.0 and a thickness of 10 nm is obtained. The amorphous silicon layer is deposited on the surface of the second low refractive index medium layer by ion-assisted deposition electron beam evaporation process. The film material uses Si particles with a purity of 99.99%, the ion source gas is Ar with a purity of 99.99%, and the working pressure is 1×10 -3 Pa, the electron gun voltage is 5kV, the substrate temperature is 50℃, and the deposition time is 8min. An amorphous silicon layer with a refractive index of 4.1 and a thickness of 5nm is obtained. The third low refractive index dielectric layer is deposited on the surface of the amorphous silicon layer by radio frequency reactive sputtering process. The sputtering target material is Si 3 N 4 Ceramic target, sputtering process gas is Ar, reaction gas is O 2 , the working pressure is 3×10 -1 Pa, sputtering power is 100w, Ar flow rate is 30sccm, O 2 The flow rate is 1 sccm, and the time for depositing the third low refractive index medium layer 6 is 20 minutes. The third low refractive index medium layer with a refractive index of 2.0 and a thickness of 100 nm is obtained, which is the flexible packaging material with structural color for depositing the counter electrode;

[0052] S3. Preparation of electrolyte: Using wet chemical sol-gel method, 30g n-butanol, 10g zinc acetate, 6g lithium perchlorate, and 18g phosphoric acid were mixed and dissolved to form a precursor solution, which was hydrolyzed and precipitated at room temperature to form a sol. After standing for 5 hours, it was evaporated at 120°C for 7 minutes to obtain a 400nm thick Li + Doped Zn(PO 4 ) x gel;

[0053] S4, the flexible substrate for depositing the working electrode prepared in step S1 and the flexible packaging material for depositing the counter electrode with structural color prepared in step S2 are coated with Li + Doped Zn(PO 4 ) xThe gel was used as the medium to bond the components together, and then a heat treatment was performed at 50°C to cure the wet chemical ion transport layer in the middle of the component for 12 minutes, and the surrounding frames were sealed with butyl glue to obtain a brown-red flexible electrochromic component.

[0054] Example 3

[0055] S1. Select flexible PET as the substrate, mix 30g Ag nanowires, 5g polysiloxane and 40g anhydrous ethanol to obtain a 6mol / L Ag nanowire solution, and spin coat it on the flexible PET by spin coating. The spin coating speed is 500r / s, the spin coating time is 30s, the thermal curing temperature is 200℃, and the curing time is 8min. A transparent conductive film with a thickness of 200nm is obtained. 16g WO 3 WO was obtained by mixing and dissolving 1 g PEDOT:PSS, 1 g acetylacetone and 3 g isopropanol. 3 / PEDOT:PSS mixed precursor solution was deposited on the first transparent conductive layer by spin coating process, the spin coating speed was 1000r / s, the spin coating time was 35s, the thermal curing temperature was 120℃, the curing time was 9min, and a composite electrochromic layer with a thickness of 300nm was obtained, which was the flexible substrate for depositing the working electrode;

[0056] S2, select flexible glass with a thickness of 30μm as flexible packaging material, mix 30g Ag nanowires, 5g polysiloxane and 40g anhydrous ethanol to obtain a Cu nanowire solution with a concentration of 6mol / L, and use spin coating process to spin coat on one side of the flexible glass, the spin coating speed is 500r / s, the spin coating time is 30s, the thermal curing temperature is 200℃, the curing time is 8min, and a transparent conductive film with a thickness of 200nm is obtained. 90 20nm NiO X Granules, 10gH 2 O 2 After being fully mixed and dissolved with 20g of anhydrous ethanol, NiO X The precursor solution was deposited on the second transparent conductive layer by spin coating process, with a spin coating speed of 800 r / s, a spin coating time of 40 s, a thermal curing temperature of 100 ° C, and a curing time of 9 min to obtain a NiO layer with a thickness of 400 nm. X Ion storage layer. On the other side of the flexible glass, the first high refractive index dielectric layer is prepared by radio frequency reactive sputtering process, the sputtering target is ZrN ceramic target, the sputtering process gas is Ar, and the reaction gas is O 2 , the working pressure is 2×10 -1 Pa, sputtering power is 100w, Ar flow rate is 30sccm, O 2The flow rate is 1 sccm, the sputtering time is 50 min, and the first high refractive index medium layer with a refractive index of 1.7 and a thickness of 150 nm is obtained. The second low refractive index medium layer is prepared on the surface of the first high refractive index medium layer by using a radio frequency reactive sputtering process, and the sputtering target material is Si 3 N 4 Ceramic target, sputtering process gas is Ar, reaction gas is O 2 , the working pressure is 10×10 -1 Pa, sputtering power is 200w, Ar flow rate is 30sccm, O 2 The flow rate was 10 sccm, and the deposition time of the second low refractive index dielectric layer was 10 min, resulting in a second low refractive index dielectric layer with a refractive index of 1.5 and a thickness of 50 nm. The amorphous silicon layer was deposited on the surface of the second low refractive index dielectric layer using ion-assisted deposition electron beam evaporation process. The film material used was Si particles with a purity of 99.99%, the ion source gas was Ar with a purity of 99.99%, and the working pressure was 1.5×10 -3 Pa, the electron gun voltage is 10kV, the substrate temperature is 150℃, and the deposition time is 30min. An amorphous silicon layer with a refractive index of 4.4 and a thickness of 20nm is obtained. The third low refractive index dielectric layer is deposited on the surface of the amorphous silicon layer by using a radio frequency reactive sputtering process. The sputtering target material is Si 3 N 4 Ceramic target, sputtering process gas is Ar, reaction gas is O 2 , the working pressure is 10×10 -1 Pa, sputtering power is 200w, Ar flow rate is 30sccm, O 2 The flow rate is 10 sccm, and the time for depositing the third low refractive index medium layer is 30 minutes, so as to obtain a third low refractive index medium layer with a refractive index of 1.5 and a thickness of 150 nm, which is a flexible packaging material with structural color for depositing the counter electrode;

[0057] S3. Preparation of electrolyte: Using wet chemical sol-gel method, 30g n-butanol, 10g zinc acetate, 6g lithium perchlorate, and 18g phosphoric acid were mixed and dissolved to form a precursor solution, which was hydrolyzed and precipitated at room temperature to form a sol. After standing for 5 hours, it was evaporated at 150°C for 9 minutes to obtain a 300nm thick Li + Doped Zn(PO 4 ) x gel;

[0058] S4, the flexible substrate for depositing the working electrode prepared in step S1 and the flexible packaging material for depositing the counter electrode with structural color prepared in step S2 are coated with Li + Doped Zn(PO 4 ) xThe gel was used as a medium to bond together, and then heat treated at 60°C, the wet chemical ion transport layer in the middle of the component was cured for 10 minutes, and the surrounding frames were sealed with butyl glue to obtain a brown-red flexible electrochromic component.

[0059] The stable cycle test of the colored state and the faded state was carried out on Examples 1-3, and the color coordinate values ​​were measured with a colorimeter. The measured results are shown in Table 1:

[0060] Table 1

[0061]

[0062] Depend on Figure 2 , 3 As can be seen from Table 4 and Table 1, the electrochromic component prepared in the embodiment of the present invention has high saturation, is not easy to fade due to aging, has a good cycle life, is easy to mass produce, and has important application value in the field of flexible electrochromic technology.

[0063] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0064] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A brown-red flexible electrochromic component, comprising a flexible substrate, a working electrode, an electrolyte, a counter electrode and a flexible packaging material with structural color, characterized in that: The working electrode includes a first transparent conductive layer and an electrochromic layer, which are sequentially deposited on a flexible substrate; the electrolyte is located between the composite color-changing layer and the ion storage layer; the counter electrode includes an ion storage layer and a second transparent conductive layer, which are sequentially deposited on one side of a flexible packaging material with structural color; the other side of the flexible packaging material with structural color is sequentially provided with a first high refractive index medium layer, a second low refractive index medium layer, an amorphous silicon layer and a third low refractive index medium layer from the inside to the outside.

2. A brown-red flexible electrochromic component according to claim 1, characterized in that: The flexible substrate and the flexible packaging material are one of flexible glass, PI and PET.

3. The brown-red flexible electrochromic component according to claim 1, characterized in that: The first transparent conductive layer and the second transparent conductive layer are both transparent conductive films made of Ag or Cu nanowires, with a thickness of 100-200 nm.

4. The brown-red flexible electrochromic component according to claim 1, characterized in that: The electrochromic layer is a composite electrochromic layer of WO3 and PEDOT:PSS, and has a thickness of 150-300nm.

5. The method for preparing a brown-red flexible electrochromic component according to claim 1, characterized in that: The steps include: S1. Select a flexible substrate, prepare an Ag or Cu nanowire solution, deposit it on the substrate by spin coating, and obtain a transparent conductive film as the first transparent conductive layer after heat treatment and curing. Deposit a WO3 / PEDOT:PSS mixed precursor solution on the first transparent conductive layer by spin coating, and obtain an electrochromic layer after heat treatment and curing, thereby obtaining a flexible substrate for depositing a working electrode; S2, prepare Ag or Cu nanowire solution, select one side of the flexible packaging material to deposit by spin coating process, heat treat and solidify to obtain transparent conductive film as the second transparent conductive layer, and deposit NiO X The precursor solution is deposited on the second transparent conductive layer by spin coating process, and the ion storage layer is obtained after heat treatment and curing. The first high refractive index dielectric layer ZrO is prepared on the other side of the flexible packaging material by radio frequency reactive sputtering process. X N Y The second and third low refractive index dielectric layers SiO are prepared by radio frequency reactive sputtering process. X N Y thin film, depositing an amorphous silicon layer on the surface of the second low-refractive index dielectric layer using an ion-assisted deposition electron beam evaporation process to obtain a flexible packaging material with structural color for depositing a counter electrode; S3. Preparation of electrolyte: n-butanol, zinc acetate, lithium perchlorate and phosphoric acid were mixed and dissolved into a precursor solution by wet chemical sol-gel method, and Li + Doped Zn(PO4) x gel; S4, the flexible substrate for depositing the working electrode prepared in step S1 and the flexible packaging material for depositing the counter electrode with structural color prepared in step S2 are coated with Li + Doped Zn(PO4) x The components are bonded together using gel as a medium, and then heat-treated to cure the wet chemical ion transport layer in the middle of the component and seal the surrounding frames with butyl glue to obtain a brown-red flexible electrochromic component.

6. The method for preparing a brown-red flexible electrochromic component according to claim 5, characterized in that: In step S1, the WO3 / PEDOT:PSS mixed precursor solution is obtained by fully mixing and dissolving WO3, PEDOT:PSS, acetylacetone and isopropanol in a weight ratio of 16:1:1:

3.

7. The method for preparing a brown-red flexible electrochromic component according to claim 5, characterized in that: In step S2, NiO X The precursor solution consists of monodispersed nanosized NiO X The particles, H2O2 and anhydrous ethanol are fully mixed and dissolved in a weight ratio of 5:10:

20.

8. The method for preparing a brown-red flexible electrochromic component according to claim 5, characterized in that: In step S2, the RF sputtering power is 100-300W, and the working pressure is 2-12×10 -1 Pa, Ar flow rate is 30sccm, and O2 flow rate is 1-10sccm.

9. The method for preparing a brown-red flexible electrochromic component according to claim 5, characterized in that: The working pressure of ion-assisted deposition electron beam evaporation in step S2 is 1-1.5×10 -3 Pa, the electron gun voltage is 5-10kV, and the substrate temperature is 50-150℃.

10. The method for preparing a brown-red flexible electrochromic component according to claim 5, characterized in that: In step S3, the weight ratio of n-butanol, zinc acetate, lithium perchlorate and phosphoric acid is 30:10:6:18.

Citation Information

Patent Citations

  • Electrochromic device in freely customizable color and application

    CN108845469A

  • Flexible electrochromic device and preparation method thereof

    CN110632803A

  • Omnidirectional reflection pure blue glass for photovoltaic building

    CN116102267A

  • Transmission type metal medium structural color film

    CN116953837A

  • Photo-sensitive composition with low reflectance

    KR1020250019195A